Species identification based on the fecal DNA samples of the Caprinae - Abdurakhim E. Kuchboev; Oybek O. Amirov; Makhamadi B. Abramatov; Bakhtiyor H. Ruziev; Mehmonjon Kh. Egamberdiyev; Rokhatoy R. Karimova (Acta Biologica Sibirica)
Fecal analysis is a useful tool for studying the species identity of rare mammals. The possibility of using non-invasive biological materials in molecular genetic studies of rare bovids is shown, using the example of the markhor and Siberian ibex of Uzbekistan. Field work including noninvasive genetic sampling collection was carried out in the study area in spring and autumn 2022-2023 in the Hissar, Surkhan State Reserves and Ugam-Chatkal State National Natural Park and Termez zoo in Uzbekistan. We used species-specific 16S rRNA mitochondrial gene fragments for polymerase chain reaction amplification for species identification. The results of the molecular analysis with the 16S rRNA mitochondrial gene allowed the identification of Capra sibirica, C. falconeri and C. hircus belonging to the subfamily Caprinae using a noninvasive genetic sampling method. This method is quite easy to use, while avoiding direct contact with the animal, which minimizes the degree of impact on the object being studied and does not require significant material and labor costs for researchers. We believe that noninvasive genetic sampling is emerging as one of the most effective and accurate methods for estimating the population size of animals, and we recommend considering this approach for endangered and rare species. The protocol developed could be a valuable tool in the management and conservation of the Capra species occurring on the Uzbekistan.